(untitled) (SCIENCE TIME JOURNAL, 2026)
Lexical expressive means and stylistic devices are key tools of linguistic expressiveness. Lexical means enrich a text through emotionally coloured word choice, while stylistic devices create patterned rhetorical effects. Their systematic use strengthens meaning, cohesion, and reader engagement.